Kingdoms of light - Foster, Alan Dean, 1946- (New York : Warner Books, 2001)
The once pristine kingdom of the Gowdlands has been conquered by the monsters of the Totumakk Horde, and the only hope for saving the kingdom lies in the final spell of a great wizard, who must die before the spell can be cast.
Library Journal.
Publisher's Weekly.
Voice of Youth Advocates (V.O.Y.A.).
Adult
Keywords: Gnomes -- Fiction; Wizards -- Fiction; Gnomes -- Fiction; Wizards -- Fiction; Fantastic fiction; Fantastic fiction